MEMBANGUN KEMANDIRIAN EKONOMI PONDOK PESANTREN MELALUI KEGIATAN KEWIRAUSAHAAN: (Studi Analisis di Pondok Pesantren Fathul ‘Ulum Puton Diwek Jombang) - Dimyati, Dimyati (TIJAROTANA : Jurnal Ekonomi dan Bisnis Syariah, 2020)
In Fathul Ulum Islamic boarding school in Jombang Diwek Puton each students who completed Alfiah given the choice to live independently by following boarding entrepreneurship program. This writing aims to explain the implementation of entrepreneurial activities in boarding school Fathul 'Ulum Puton Diwek Jombang as a means of building independence Pondok pesantren economics and know the supporting factors and inhibitors in an effort to build economic independence boarding school through entrepreneurial activities in boarding school Fathul' Ulum Puton Diwek Jombang. The type of research the writer uses is field research and library research, primary data collected through interviews, observation and documentation, how to approach wear phenomenology, and the method used to analyze the data is descriptive method normative.In building a boarding school can not be separated from the name of the cost, therefore boarding school Fathul Ulum Puton Diwek Jombang obtain these costs through entrepreneurship is done by kyai who as manager and santri as manager. Not a few areas of entrepreneurship in the work but there are several areas of entrepreneurship. Every entrepreneur is sheltered by BUMP (Badan Usaha Milik Pesantren), this institution regulates every way entrepreneurship and body that agree if there is a new business that will be done by santri. For capital in entrepreneur santri cooperate with BMT Al-Amin by using Mudharabah contract.